Effect of the umbilical cord length on mode of delivery and perinatal outcome - Saidani, Syeda Mahin; Sajjan, Gowramba; Azeem, Mohammed Abdul (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: The umbilical cord is a vital anatomical structure connecting the fetus to the placenta, and its length along with the presence of nuchal loops may influence labor progression and neonatal outcomes. This study aimed to evaluate the relationship between umbilical cord length and mode of delivery, duration of labor, neonatal APGAR scores, NICU admissions, and incidence of fetal distress. Methods: A prospective observational study was conducted at Al-Ameen medical college hospital from July 2023 to January 2025, involving 200 pregnant women. Umbilical cord length and the presence and number of nuchal loops were documented at delivery. Maternal and neonatal outcomes, including mode of delivery, labor duration, fetal distress, and neonatal parameters, were recorded and analysed statistically. Results: The mean umbilical cord length was 50.68±11.75 cm. Although the incidence of caesarean delivery was higher in both short and long cord groups, the difference was not statistically significant (p=0.217). Labor duration was significantly prolonged in cases with nuchal cord, particularly among primigravida (17.62±1.38 h vs. 11.95±1.49 h). Neonates with nuchal loops had lower APGAR scores at 1 and 5 minutes (p=0.003), and NICU admission rates were higher among those with multiple loops (p<0.001). Fetal distress increased significantly with number of nuchal loops (p<0.0001). Conclusions: Abnormal cord length and multiple nuchal loops are significantly associated with prolonged labor, fetal distress, increased incidence of instrumental delivery, caesarean section due to cephalopelvic disproportion due to deflexed head, low APGAR score, NICU admission. Patients with 2-3 loop of cord around the neck can have normal vaginal delivery. There is increasing rate of caesarean section due to ultrasound diagnosis of cord around the neck at term, because of obstetrician distress and patients request rather than obstetric indication.